THE GLOBAL FINANCIAL CRISIS AND METAPHORS: A Contrastive Analysis Of English, Serbian and Romanian - Silaški, Надежда; Kilyeni, Annamaria (Наслеђе, 2012)
Under the theoretical wing of Conceptual Metaphor Theory, as initiated by Lakoff and Johnson (1980), in this paper we set out to comparatively investigate the conceptual metaphors used for the conceptualisation of the global economic and financial crisis in English, Romanian and Serbian print and electronic media reporting in the period 2008–2010. By adopting a cross-linguistic and cross-cultural approach to metaphor analysis in popular economic and business discourse, our main aim is to establish whether the same conceptual metaphors are used in English, Romanian and Serbian for the conceptualisation of the most severe economic crisis since the Great Depression, or, alternatively, whether any culture-specific aspects may be found in the three languages. We also focus on any influence English, as well as the culture determined by the English language, may exert on Romanian and Serbian as regards conceptual and linguistic metaphors serving to structure the understanding of the global financial crisis.